Design of Wind/Diesel Generator Micro-Grid Power System in Kano, Nigeria, Using Homer - Mohammed, Nuhu; Bello Adisa, Ademola; Ahmed Bawa, Mohammed; Dandakuta, Habou (International Journal of Engineering and Technology, 2018)
A micro-grid system has been designed using wind/diesel generators power sources. The system is aimed to cater for the electricity demand of Kwankwasiyya city Kano, Nigeria. The city has about 400 housing units with average daily electricity demand of 10000 kWhr. The project employed the use of homer, a software that performs Hybrid Optimization Model for Electric Renewables. The most appropriate system architecture was chosen from the optimisation result based on the selection factors set (initial investment cost, total electrical production to site primary demand ratio and so on). A system comprising single wind turbine (800 kW), and two generators of 400 kW and 300kW has been selected based on the selection criteria. The electrical output shows that 82% of the total production will be consumed onsite with the remaining would be sold to the grid. The system has a cost of energy value of 0.279 kWh with net present cost of about 11,000,000. The system is economically viable considering the need of reliable power in the region even though, the price of the electricity is higher than what is obtainable from the grid.Â Â